Physicochemical and Pharmacokinetic Property Prediction of Substances in Centella asiatica using pkCSM: Prospects for the Creation of Therapeutic Formulations from Plant Isolates - Faisal Akhmal Muslikh; Fendy Prasetyawan; Rosa Juwita Hesturini; Fita Sari; Anis Akhwan Dhafin; Muhammad Alviyan Shutiawan; Elsa Mahardika Putri; Okky Intan Mawarni (International Journal of Global Sustainable Research, 2023)
Indonesia is a megabiodiversity country with the second-largest abundance of biodiversity in the world. Centella asiatica (CA) is an important medicinal herb used in various countries in the world. It is known to have good pharmacological activity, but more scientific data is still needed to justify its increasing use, especially regarding its pharmacokinetics and safety. The aim of the research was to predict the physicochemical and pharmacokinetic properties of the compounds contained in CA. The compound content was obtained from journal references that collected information from Dr. Duke's Phytochemical and Ethnobotanical Database, then each compound was subjected to physicochemical and pharmacokinetic analysis using a web tool. The results show that the compounds quercetin and kaempferol are compounds that have good physicochemical and pharmacokinetic properties compared to other compounds contained in CA.